A ballistic impact model for evaluating a preliminary higher level from simulation and tests on a glass fibber composite. Issue 1 (1st October 2022) - Ojoc, G G; Titire, L Chiper; Pirvu, C; Popescu, C
Abstract : This paper presents a discussion on simulating the impact projectile – target, for a velocity of 375 m/s and a comparison to actual stratified panels. Model is run in Explicit Dynamics (Ansys), with material constitutive models as isotropic bilinear hardening, the failure criterion being the equivalent plastic strain at break. Dependence on elastic properties of temperature is not available in simulations that use explicitly dynamic systems. Only one value is used for a property. These temperature dependent values will be used by the solver. The first values defined as temperature-dependent data will be used in numerical solving. In the case of projectile impact-protection panel, the use of properties without temperature dependence is justified by recordings with thermal cameras, by the results of models presented in the literature and the characteristics of the materials used for the panels, some of which (such as aramid or glass fibber composites), having constant properties over a fairly large temperature range. From the documentary study, the modelling of a bullet impact calibre (9 mm or 7.62) in the impact domain targeted by the author is analysed under isothermal conditions. There is a thermal effect, but it is considered weak as compared to the failure mechanisms of the involved solids (breaking, deformation, delamination, friction). There were simulated and tested panels made of 8 and 16 layers, considered bonded with breakable condition in tensile stress. The actual panels are made of quadriaxial fabrics of glass fibbers, bonded by laying-up and pressing with an epoxydic resin. From the results obtained for these runs, the following conclusions could be drawn: (I) although the layer material model was simplified to a isotropic bilinear hardening model with data from the literature, the results were validated by the number of layers destroyed for the partially penetrating plates and by the size of the delamination on the back of the last layer and (II) based on the results for panels modelled and actually tested, cases with intermediate thicknesses could be rolled in order to optimize the surface density of the protective panel.